2022
DOI: 10.1111/all.15223
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of non‐allergic rhinitis phenotypes in the general population: A cross‐sectional study

Abstract: Background Non‐allergic rhinitis (NAR) can be subdivided into several phenotypes: rhinorrhea of the elderly, rhinitis medicamentosa, smokers', occupational, hormonal, drug‐induced, gustatory, and idiopathic rhinitis. There are two pathophysiological endotypes of NAR: inflammatory and neurogenic. Phenotypes may serve as an indicator of an underlying endotype and, therefore, help to guide the treatment. The prevalence of each phenotype in the general population is currently unknown. Methodology/Principal Cross‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Three studies conducted in Belgium, Sweden and Italy found very similar prevalences of NAR, between 9.6% and 12.0% [ 21 23 ]. Recently, a study in the Netherlands found a prevalence of NAR of 26% [ 7 ]. The actual prevalence of rhinitis may be underestimated because most studies had only considered AR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies conducted in Belgium, Sweden and Italy found very similar prevalences of NAR, between 9.6% and 12.0% [ 21 23 ]. Recently, a study in the Netherlands found a prevalence of NAR of 26% [ 7 ]. The actual prevalence of rhinitis may be underestimated because most studies had only considered AR.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of this knowledge on rhinitis is derived from clinical practice, and there are few epidemiological studies in the general adult population that have assessed the prevalence and characteristics of phenotypes of rhinitis. Furthermore, few of them have assessed NAR [ 3 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…NAR comprises a large heterogeneous group of patients without systemic signs of allergic inflammation (allergen-specific IgE in the blood and/or positive SPT results) or clinical signs of infection. Of these cases, up to 50% do not have a clear etiology underlying the symptoms and are defined as idiopathic rhinitis (IR) [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most patients complained of discomfort during meals because of rhinorrhea. These symptoms could be defined as non-allergic rhinitis, a type of chronic rhinitis (CR) that causes rhinorrhea, nasal obstruction, sneezing, and/or itchy nose without any clinical evidence of infection or allergic diseases ( 5 ). Non-allergic rhinitis is affected by the sympathetic and parasympathetic nervous system of the nasal cavity, and rhinitis symptoms are thought to develop due to autonomic dysfunction that occurs after stroke ( 6 ).…”
Section: Introductionmentioning
confidence: 99%